Attitude of HE Students Towards Privatisation of Higher Education: A Study - Kumar, Lalit; Kumar, Sudhir (JOURNAL OF INDIAN EDUCATION, 2010)
Several researches have shown that attitude has its bearing on so many attributes and capabilities [Kumar (1994, 1998), Singh and Sharma (1995)]. Several other studies have reflected that different variables have their bearing on different types of Attitude [Krishna and Rao (1992), Kumar (1995, 1996, 2003, 2007)] and that is why the researchers undertook this study. In the present study to measure the attitude of higher education students towards privatisation of higher education the tool developed and standardised by Kumar, Lalit. (Attitude Towards Privatisation of Higher Education Scale) has been used to collect the data. In this survey type of research 500 higher education students have been taken as sample by using Stratified Random Sampling Technique. Statistics like Percentage, Mean, Standard deviation and t-value have been calculated to test the hypotheses. The study reveals that most of the Higher Education students do not possess favourable attitude Towards Privatisation of Higher Education and types of courses, Category and Types of Institutions have their bearing on Attitude Towards Privatisation of Higher Education.